A multicenter dosimetry study to evaluate the imaging dose from Elekta XVI and Varian OBI kV-CBCT systems to cardiovascular implantable electronic devices (CIEDs). (November 2018) - Aslian, Hossein; Delana, Anna; Kaiser, Stefano Ren; Moretti, Eugenia; Foti, Claudio; Bregant, Paola; de Denaro, Mario; Longo, Francesco; Severgnini, Mara
Highlights: The potential contribution of imaging dose from kV-CBCT to the CIED was evaluated. Three dosimeters were considered in a multi-center study, XRQA2, MOSFET and TLDs. Detailed results of imaging doses to CIED from different CBCT-protocols were found. An approach for more accurate risk classification of CIED patients was suggested. Abstract: The increasing use of daily CBCT in radiotherapy has raised concerns about the additional dose delivered to the patient, and it can also become a concern issue for those patients with cardiovascular implantable electronic devices (CIEDs) (Pacemaker [PM] and Implantable Cardioverter Defibrillator [ICD]). Although guidelines highly recommend that the cumulative dose received by CIEDs should be kept as low as possible, and a safe threshold based on patient risk classification needs to be respected, this additional imaging dose is not usually considered. Four centers with different dosimetry systems and different CBCT imaging protocols participated in this multicenter study to investigate the imaging dose to the CIEDs from Elekta XVI and Varian OBI kV-CBCT systems. It was found that although imaging doses received by CIEDs outside the CBCT field are negligible, special attention should be paid to this value when CIEDs are inside the field because the daily use of CBCT can sometimes contribute considerably to the total dose received by a CIED.